The Influence of Transformational Leadership Style and Organizational Commitment on Loyalty with Job Satisfaction as an Intervening Variable in Employees of CV. Amanda Brownies - Ryco Julianboy Parinding; Mappamiring Mappamiring; Akhmad Muhammadin (Transpublika Publisher, 2025)
The objective of this research is to analyze how transformational leadership, organizational commitment, and job satisfaction impact loyalty. It also looks at how transformational leadership and organizational commitment affect job satisfaction. Additionally, it examines the indirect impact of transformational leadership and organizational commitment on loyalty, with job satisfaction acting as a mediator. The study focuses on employees at CV. Amanda Brownies and utilizes questionnaires to collect primary data from a sample size that is saturated. The survey involves 100 participants. The validity and reliability of the questionnaire results were assessed through the PLS model and model evaluation. Various tests were conducted including determinant coefficient tests, model goodness of fit tests, and hypothesis tests, both directly and indirectly. The data processing was completed using SmartPLS version 3. The study's findings clearly indicate that transformational leadership, commitment to the organization, and job satisfaction all have a positive and impactful influence on loyalty. Additionally, the study suggests that transformational leadership specifically contributes to loyalty through job satisfaction, while organizational commitment has no direct impact on loyalty through job satisfaction.